1984
DOI: 10.1080/00049538408255316
|View full text |Cite
|
Sign up to set email alerts
|

Processing of proprioceptive information in Parkinson's disease patients

Abstract: The present study is concerned with a comparison of Parkinson's disease patients and normal subjects on a number of simple and choice reaction time tasks in accordance with Sternberg's interactive procedures. The results indicated that the motor disorder in Parkinson's disease was at the level of output processing and related to the inability of central mechanisms to select and organize responses. Further, the results suggested that patients had difficulty in formulating complex plans or programmes for action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The failure to effectively influence the response selection process in Experiment 1 may, to some extent, have been associated with the SIR2 task which was designed to load this process by forcing subjects to choose between two possible responses. This task has been used successfully with adults by Glencross and Koreman (1979) and by Glencross and Tsouvallas (1984). but it is possible that in the present study children experienced difficulty with the requirements of this task.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The failure to effectively influence the response selection process in Experiment 1 may, to some extent, have been associated with the SIR2 task which was designed to load this process by forcing subjects to choose between two possible responses. This task has been used successfully with adults by Glencross and Koreman (1979) and by Glencross and Tsouvallas (1984). but it is possible that in the present study children experienced difficulty with the requirements of this task.…”
Section: Discussionmentioning
confidence: 97%
“…These were attached to pins inserted into solenoids which, when operated, allowed the arm to fall suddenly, extending at the elbow. This technique has been used previously by Glencross and Koreman (1979) and Glencross and Tsouvallas (1984). Curtains on either side of the subject precluded vision of arm movements.…”
Section: Apparatus and Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a physical disorder complicates the assessment of mental disorder, and the boundary between the two becomes blurred. For example, it has been suggested that the motor disorder is at the level of cognitive processing, that the central control processes are unable to select and organize responses, and that PD subjects have problems in formulating complex plans for action (Glencross & Tsouvallas, 1984). A delay in reaction time, for instance, might reflect a deficit in motor programming at the level of the construction of the program, its maintenance in store for use, or in its delivery to the muscles (Marsden, 1989).…”
Section: Discussionmentioning
confidence: 99%